Ecology and management of large patch of zoysiagrass, caused by Rhizoctonia solani AG 2-2 LP - Obasa, Kehinde Christopher (Kansas State University, 2012)
Large patch, caused by the fungus Rhizoctonia solani anastomosis group (AG) 2-2 LP, is the most common and severe disease of zoysiagrass (Zoysia spp). Despite the importance of this disease, few studies have examined pathogen biology, cultivar susceptibility, cultural controls, and chemical controls. The objectives of this dissertation were: (1) Characterize large patch isolates based on anastomosis pairing, in-vitro mycelial growth rates, nuclear counts, virulence, PCR, and amplified fragment length polymorphism (AFLP); (2) Determine the effects of cultivation (aerification, verticutting, and sand topdressing) on disease severity; (3) Evaluate different fall and spring applications of the fungicides flutolanil, azoxystrobin, and triticonazole; (4) Evaluate the susceptibility of fifteen new zoysiagrass germplasm lines from parental crosses including Z. japonica, Z. matrella, and Z. pacifica. All the R. solani isolates from large patch-infected zoysiagrass from Kansas belonged to AG 2-2 LP. Variations were observed among the isolates in their average number of nuclei per cell, mycelial growth rates and virulence. There was also variation in the amplified fragment length polymorphism (AFLP) DNA fingerprints, suggesting possible underlying genetic differences of biological significance among members of AG 2-2 LP. Cultivation did not affect soil moisture or temperature. Cultivation also did not reduce patch sizes, nor influence turf recovery rate from large patch. From 2009 to 2011, spring and fall N fertility was consistently associated with lower percentages of diseased turf in both cultivated and non-cultivated plots at Manhattan and Haysville. In general, two fall applications of fungicide did not reduce disease compared to one fall application. Fungicides applied in the fall when thatch temperatures ranged from 17.8oC to 23.2oC reduced disease compared to untreated controls. Early spring applications reduced disease compared to later spring applications. In germplasm screening studies, all progeny had similar disease levels compared to Meyer in the growth chamber, but only 6 consistently had disease levels as low as Meyer in the field. Growth chamber results did not correlate to field results.
Keywords: Rhizoctonia solani; Zoysiagrass; Fungicide application timing; Large patch susceptibility of freeze-tolerant zoysiagrass genotypes; Cultural practices; Characterization of large patch-rhizoctonia isolates; Ecology (0329); Management (0454); Plant Pathology (0480)